The Effect of the Level of Development of Third Party Funds (DPK) and Return On Assets (ROA) on Musyarakah Financing at Bank BCA Syariah for the 2018-2022 Period - Rizma Denytasari; Muhamad Fahmi Azizul Farhan; Binti Nur Asiyah (Jurnal Syntax Transformation, 2023)
This study aims to examine the direct influence of the level of development of Third Party Funds (DPK) and Return On Assets (ROA) on Musyarakah Financing at Bank BCA Syariah for the 2018-2022 period. This research uses quantitative data types. The data in this study are secondary data. Secondary data is in the form of financial statements at Bank BCA Syariah published in 2018-2022. This study used secondary data where the data was obtained by non-participant observation. The results showed that the variables that affect musharakah financing are based on the test table t the level of development of Third Party Funds (DPK) X1) on Musyarakah Financing (Y) where the significance value (Sig) X1 is 0.001 < 0.05 and the t value is calculated 28,795 > t table 4,303, it can be concluded that H1 is accepted. Furthermore, the Level of Development of Third Party Funds (X1) and Return On Assets (X2) simultaneously on Musharakah Financing (Y) where based on the F test table the significance value (Sig) for the effect of the Level of Development of Third Party Funds (X1) and Return On Assets (X2) simultaneously on Musharakah Financing (Y) is 0.002 < 0.05 and the value of F is calculated at 511,539 > F table 9.55, it can be concluded that H3 is accepted. While the variable that does not affect musharakah financing is Return On Assets (X2) to Musharakah Financing (Y) where based on the test table t significance value (Sig) Return On Assets (X2) of 0.452 > 0.05 and t value calculated 0.926 < t table 4.303, it can be concluded that H2 is rejected.